Mediation of Memory and Cultural Practices: two Croatian Cases - Škrbić Alempijević, Nevena (Array, 2013)
This paper analyzes the role of cultural practices in the process of memory construction and circulation. Public celebrations and festivals are seen as arenas in which different agents, from political elites and national institutions to tourist boards and nongovernmental organizations, attach new meanings to images of the past. My aim is to show how individuals participating in those practices come to terms with, negotiate or subvert dominant representations of history. I also pay attention to the relationship between the politics of memory and identitary practices of local inhabitants. Two Croatian cases, related to the production of heritage in birthplaces of notable historical figures, are used to examine these issues. One approaches Kumrovec, a birthvillage of ex-Yugoslav President Josip Broz Tito, as a realm of memory in socialism and on its treatment after the breakup of the former Yugoslavia. The importance of the Day of Youth, a celebration of Tito's proclaimed birthday still taking place nowadays, is highlighted. The other deals with Ogulin, a town branded as the Homeland of Fairytales due to the fact that Ivana Brlić Mažuranić, an eminent writer of fairytales, was born there. The focus is on the Ogulin Fairytale Festival as a means by which the memory of the writer comes to life in urban space. Although symbols incorporated in heritage production in those places are different, analysis of mnemonic practices in the two cases reveals a variety of ways in which institutions and individuals design and use public events to create and mediate cultural memory.